Analisis Portofolio Optimal Saham Syariah Menggunakan Multi Index Models (Periode: 04 Januari 2010 â 1 Juli 2013) - ArjaÃ¢Â€Â™i, Mulat; Qudratullah, Mohammad Farhan (UIN Sunan Kalijaga Yogyakarta, 2013)
The portfolio is a combination or aggregation of two or more individual stock and concern for investors is to form the optimum portfolio and one of the ways that can be used are Multi-Index Models (MIM). This Model is a development of the Single Index Models (SIM), if on a SIM only consider one factor that affects the value of the stock, then return at MIM considers more than one factor. This study discusses the optimal portfolio analysis using Multi-Index Models with a case study on the stock of the Sharia Jakarta Islamic Index (JII) period 4 January 2010 â 1 July 2013 by using composite stock price index (IHSG), index Dow Jones Industrial Average (DJIA) and index the Hang Seng Index as a factor in MIM. The results of this research were obtained that the optimum portfolio is a portfolio that was created based on the stocks that had the highest positive return value, i.e. UNVR 41,40%, SMGR 40.66%, KLBF 11.01, and LPKR 6,93% with a value of expected return portfolio amounted to 2.55% and risk of a portfolio of 0,29%.